Analysis of Determinants in the Development of the Medan-Binjai Elevated Railway and Its Contribution to Regional Development: English - Purba, Werdayani Br; Nasution, Zulkifli; Lubis, Satia Negara (CV. ARGA FARMA, 2025)
The development of the Medan-Binjai elevated railway is a strategic initiative aimed at enhancing mass transportation efficiency, reducing traffic congestion, and supporting regional development in Medan City. This study identifies key factors influencing the project's success and evaluates its contributions to regional growth. Using quantitative methods, including factor analysis and descriptive statistical evaluations, data were collected through surveys and interviews with 40 respondents comprising government officials, transportation experts, railway operators, and economic stakeholders. The findings reveal that environmental factors (48.57%) and planning human resources (21.14%) are the dominant determinants. Environmental factors emphasize the importance of reducing congestion and promoting eco-friendly transportation, while human resource factors highlight the role of competent planners. System, technology, and funding factors also support the project's success. The project has significant social, economic, and environmental impacts, such as improved accessibility, new employment opportunities, and reduced carbon emissions. Aligned with the Regional Spatial Plan (RTRW) 2010–2030, this project enhances connectivity within the Mebidangro metropolitan area and serves as a model for sustainable infrastructure development in Indonesia. Recommendations include strengthening stakeholder collaboration, promoting multimodal integration, and conducting further studies to evaluate the project's long-term impacts after its operation.